A Lipoxygenase 3 mutation reverses growth phenotypes in an Arabidopsis Plastid Lipase 3 overexpression line - Yosia Mugume; Ron Cook; Breana Hagerty; Jinjie Liu; Zachary B. Alvord; Linda Danhof; John E. Froehlich; Josh V. Vermaas; Christoph Benning (PLoS ONE, 2026)
Plastid Lipase 3 (PLIP3) is a chloroplast phospholipase A that cleaves linolenic acid, a polyunsaturated fatty acid, from the sn -1 position of the chloroplast membrane lipid monogalactosyldiacylglycerol. Linolenic acid is subsequently converted by enzymes in the chloroplast and the peroxisome to jasmonic acid (JA) requiring transport between the organelles. Overexpression of a cDNA encoding PLIP3 resulted in stunted plant growth with altered leaf morphology caused by accumulation of JA and other oxylipin metabolites redirecting the metabolism from growth to defense. We conducted a genetic suppressor screen in the PLIP3 -OX ( PLIP3 overexpression) line to query the entire pathway from the start of JA biosynthesis to its perception, transduction, and modification by other signaling pathways. We identified a mutant allele of the 13-lipoxgenase LOX3, lox3–4 , that is causal to the attenuation of the PLIP3 -OX phenotype with reduced dwarfism and decreased production of JA and other oxylipins. The responsible G776E point mutation is in the C terminal catalytic domain in proximity to the non heme iron binding site of LOX3. The point mutation likely inhibits the oxidation of α-linolenic acid demonstrating its importance for general JA biosynthesis as its activity cannot be compensated for by other 13-lipoxygenases.